Spatial distributions and determinants of intimate partner violence among married women in Ethiopia across administrative zones - Meseret Tadesse Fetene; Senait Cherie Adgeh; Haile Mekonnen Fenta (PLoS ONE, 2025)
Background Intimate partner violence (IPV) against women is highly prevalent in the world, especially in low-middle-income countries including Ethiopia. Studies so far assessing risk factors for IPV often use the classical model without geographical location information and spatial effects. This study aimed to estimate the overall prevalence and associated risk factors of intimate partner violence among Ethiopian administrative zones. Method The 2016 Ethiopian Demographic and Health Survey (EDHS) data were used. The primary outcome of the study was the experience of different types of IPV: physical, emotional, and sexual by ever-married women aged 15–49 years. We adopted a generalized multilevel mixed model with IPV as an outcome variable and zones as random effects. Results The prevalence of physical, emotional, and sexual violence in Ethiopia are respectively 20.38%, 22.31%, and 7.58%. The result indicated that 1,423 (30.15%) of respondents had experienced at least one of the three types of IPV. Women who had older age had more children, had lower decision-making power, and had a husband who was a drinker and had controlling behavior were more likely to experience any forms of IPV. Significant zone-wise spatial variations of IPV were also observed. Conclusions The distribution of IPV in married women varies among Ethiopian administrative zones. Several factors were associated with IPV, therefore, interventions targeting the hotspot areas and specific determinant factors should be implemented by the concerned bodies to reduce IPV among married women in the population.